Pengaruh Gaya Kepemimpinan Demokratis dan Pengembangan Karir Terhadap Kepuasan Kerja Pada Karyawan Generasi Z - Merry Moy Mita (Jurnal Ilmu Manajemen METHONOMIX, 2026)
The influx of Generation Z into the workforce introduces a new paradigm, demanding significant adjustments in management systems, particularly concerning leadership and career development. This study aims to analyze the influence of democratic leadership style and career development on the job satisfaction of Generation Z employees. A quantitative method with a causal design was employed, utilizing a survey of 150 Gen Z respondents in Medan, selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS 25. The results demonstrate that both democratic leadership and career development have a significant positive partial effect on job satisfaction. Simultaneously, these variables also exert a significant combined influence, with a Coefficient of Determination (R²) of 0.589, indicating that 58.9% of the variation in job satisfaction can be explained by these two factors. A key finding reveals a synergistic effect; empowering democratic leadership acts as a catalyst that maximizes the benefits of career development programs. The practical implication of this study underscores the necessity for organizations to strategically integrate both approaches to create a work ecosystem that not only satisfies but also fosters loyalty and reduces turnover intention among Generation Z employees.